Governors' term of office and information disclosure: Evidence from Japan - Eiji Yamamura (Economics and Econometrics Research Institute (EERI), 2016)
Local governors who hold office for longer periods are thought to be more likely to collude with various groups to increase their own benefit through long-term interaction. There is no term limit for local governors in Japan, seemingly causing such collusive behavior. However, since 1987, local government at the prefecture level has begun to promulgate public information disclosure ordinances, which is anticipated to prevent collusive behavior. As of 2001, all 47 local governments have promulgated their local ordinances. This paper uses a prefecture-level dataset from 1987 and 2001 to explore whether the number of years that local governors hold office is associated with the timing of the promulgation of public information disclosure ordinances. The major finding using survival regression analysis is that the longer local governors hold office, the less likely the ordinance is promulgated. This highlights the policy implication that the term of local governors should be limited.
Keywords: G38; P48; C41; 330; Multiple terms; information-disclosure ordinance; collusion; survival regression analysis